2014
DOI: 10.2741/4212
|View full text |Cite
|
Sign up to set email alerts
|

Nek2 and Plk4: prognostic markers, drivers of breast tumorigenesis and drug resistance

Abstract: The Nek2 and Plk4 kinases serve as crucial regulators of mitotic processes such as the centrosome duplication cycle and spindle assembly. Deregulation of these processes can trigger chromosome instability and aneuploidy, which are hallmarks of many solid tumors, including breast cancer. Emerging data from the literature illustrated various functions of Nek2 in breast cancer models, with compelling evidence of its prognostic value in breast tumors. The two kinases control distinct steps in the centrosome-centri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 102 publications
3
96
0
Order By: Relevance
“…Even though our results indicate that centrosome amplification is a redundant function of the E2F activators, our findings are relevant to the understanding of breast carcinogenesis, since E2F1, E2F3, and Nek2 are frequently overexpressed in breast tumors (26,97) and negatively impact the outcomes of survival (16,56,98). In fact, interference with Nek2 overexpression suppresses tumorigenesis of breast cancer cells (99).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Even though our results indicate that centrosome amplification is a redundant function of the E2F activators, our findings are relevant to the understanding of breast carcinogenesis, since E2F1, E2F3, and Nek2 are frequently overexpressed in breast tumors (26,97) and negatively impact the outcomes of survival (16,56,98). In fact, interference with Nek2 overexpression suppresses tumorigenesis of breast cancer cells (99).…”
Section: Discussionmentioning
confidence: 89%
“…Using data presented in Fig. 1a Ϫ (MCF7 and T47D), and triple-negative (MDA-MB-231 and MDA-MB-468) cell lines do not display centrosome amplification (56,62). MCF10A cells are used as a control, since they are nontransformed, immortalized human mammary epithelial cells that lack the p16 INK4A and p14 INK4B tumor suppressors and display normal p53 activity (66,67).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All four members (Plk1-4) of this serine/threonine protein kinase family share sequence similarity and domain structure with the founding member, Drosophila Polo kinase (the homolog of human Plk1) (4). Plks are highly expressed in proliferating cells and are overexpressed in a variety of cancers where they have the potential to promote chromosomal instability and tumorigenesis (5)(6)(7)(8)(9). Previous studies have shown that Plk kinase activity can be limited to brief periods within the cell cycle through mechanisms involving the transcription, localization, degradation, and autoinhibition of the kinase (3,(10)(11)(12)(13).…”
mentioning
confidence: 99%